Dissipation processes in the Tongue of the Ocean. Issue 5 (14th May 2016) - Hooper, James A.; Baringer, Molly O.; St. Laurent, Louis C.; Dewar, William K.; Nowacek, Doug
Abstract: The Tongue of the Ocean (TOTO) region located within the Bahamas archipelago is a relatively understudied region in terms of both its biological and physical oceanographic characteristics. A prey‐field mapping cruise took place in the fall between 15 September 2008 and 1 October 2008, consisting of a series of transects and "clovers" to study the spatial and temporal variability. The region is characterized by a deep scattering layer (DSL), which is preyed on by nekton that serves as the food for beaked whale and other whale species. This study marks the first of its kind where concurrent measurements of acoustic backscatter and turbulence have been conducted for a nekton scattering layer well below the euphotic zone. Turbulence data collected from a Deep Microstructure Profiler are compared to biological and shear data collected by a 38 kHz Simrad EK 60 echo sounder and a hydrographic Doppler sonar system, respectively. From these measurements, the primary processes responsible for the turbulent production in the TOTO region are assessed. The DSL around 500 m and a surface scattering layer (SSL) are investigated for raised ε values. Strong correlation between turbulence levels and scattering intensity of prey is generally found in the SSL with dissipation levels as large as ∼10 −7 W kg −1, 3 orders of magnitude above background levels. In the DSL and during the diel vertical migration, dissipation levels ∼10 −8 W kg −1 were observed. Key Points: Large biomass layer shows raised dissipation values between 400 and 600 m Biomass shown to be potentially important in the global energy budget